2015
DOI: 10.1039/c4cc09180a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal C–H borylation using a CO-free iron boryl complex

Abstract: New CO-free iron boryl complexes, CpFe(PR3)2(Bpin), are described. The CpFe(PEt3)2(Bpin) derivative is uniquely capable of UV-free arene borylation at 70 °C via a dissociative pathway. Catalytic C-H borylation does not proceed using either monometallic or heterobimetallic schemes, and this failure is rationalized through analysis of relative pKa values for the corresponding iron hydride species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…18 In fact, complete removal of the SBCO ligands from the catalyst design shuts off C-H borylation catalysis. 19 While the structural identification and parameterization of SBCO ligands is decades old, a rigorous analysis of their structural data in the broad context of bimetallic carbonyl complexes has not been undertaken since the advent of easily searchable structural databases and the large datasets they provide. 20 In this article, we briefly summarize the history of SBCO structures, provide a re-evaluation of this literature based on a data-intensive search of the Cambridge Structural Database (CSD), and present computational data clarifying the strength (or lack thereof ) of the SBCO interaction.…”
Section: Neal P Mankadmentioning
confidence: 99%
“…18 In fact, complete removal of the SBCO ligands from the catalyst design shuts off C-H borylation catalysis. 19 While the structural identification and parameterization of SBCO ligands is decades old, a rigorous analysis of their structural data in the broad context of bimetallic carbonyl complexes has not been undertaken since the advent of easily searchable structural databases and the large datasets they provide. 20 In this article, we briefly summarize the history of SBCO structures, provide a re-evaluation of this literature based on a data-intensive search of the Cambridge Structural Database (CSD), and present computational data clarifying the strength (or lack thereof ) of the SBCO interaction.…”
Section: Neal P Mankadmentioning
confidence: 99%
“…We were successful in synthesizing several CpFe(PR 3 ) 2 (Bpin) derivatives and found that Cp-Fe(PEt 3 ) 2 (Bpin) was able to borylate arene solvents in the absence of light at temperatures as low at 70 °C. 54 Unfortunately, catalysis was not possible in this case because the byproduct of C-H borylation, CpFe(PEt 3 ) 2 H, was not observed to react with any (NHC)CuH partner (Scheme 2), thus eliminating the possibility of a thermal analogue of the cycle shown in Scheme 1c. The facile H 2 elimination reaction in our original system was driven by the hydridic…”
Section: Pursuit Of Thermal Borylation Conditionsmentioning
confidence: 99%
“…Direct C(sp 2 )-H borylation offers a simple and efficient route to aryl-boronic esters, which are key platforms for organic synthesis [13][14][15]. Iridium-based complexes have become a "go-to" for C(sp 2 )-H borylation reactions [16][17][18][19][20][21][22][23][24], while the discovery and development of Earth-abundant alternatives remains comparatively rare [25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%